Proposition of an equivalent reduced thickness for composite steel plate shear walls containing an opening - Meghdadian, Mohammad; Gharaei-Moghaddam, Nima; Arabshahi, Alireza; Mahdavi, Navid; Ghalehnovi, Mansour (Journal of constructional steel research, 2020)
The composite steel plate shear wall (CSPSW) is a relatively new structural system which attracted many researchers in recent years. The main idea for developing the CSPSW system is to improve out-of-plain strength of steel plate shear walls by addition of one or two layers of concrete. This configuration provides high strength and acceptable ductility for this system in comparison with the other lateral load bearing systems. Sometimes due to architectural considerations, it is required to include openings in the shear walls. These openings change performance of the CSPSW and reduce its strength and stiffness. Moreover, inclusion of openings offers difficulty in analysis and design of the CSPSW system. The main goal of this study is to develop accurate numerical models to analyze CSPSW containing opening. Based on the obtained result and using an evolutionary algorithm named Multi-Expression Programming (MEP), an empirical relation is proposed to calculate equivalent reduced thickness to be used in the analysis of the CSPSW instead of incorporating the opening in the developed models. Accuracy of the developed model and the proposed relation are verified experimentally. •Effects of opening on performance of composite steel plate shear walls is investigated.•A relation to calculate reduced equivalent thickness instead of modeling opening in the wall is proposed.•Accuracy of the suggested model is verified experimentally.•Performance of the equivalent reduced thickness on multi-story walls is investigated.